An unusual case of bilateral reversible blindness in a child: Crucial role of imaging - Rohilla, Seema; Yadav, Rohtas K.; Rawal, Manoj; Das, Kunal; Dhaulakhandi, Dhara B. (Journal of Pediatric Neurology, 2011)
Sphenoid sinusitis is an unusual cause of blindness and may go undetected if the sinusitis is otherwise asymptomatic. Radiological studies can play a very crucial role in the diagnosis of such cases. Here we present one such case where radiologic diagnosis was critical to determining the treatment plan. A 12-year-boy developed sudden blindness and right sided hemiparesis one week after the episode of fever. Imaging studies attributed his symptoms to acute sphenoiditis and thrombus in cerebral veins. Early institution of proper medical treatment based on correct radiological diagnosis led to reversal of his symptoms within two days.
Keywords: Acute sphenoiditis; reversible visual loss; cerebral venous thrombosis